Betty Lee, Freshman - Grove, Harriet Pyne (Salt Lake City, UT : Project Gutenberg, 2010)
"Betty Lee, Freshman" by Harriet Pyne Grove is a novel written during the early 20th century. The story centers around a young girl named Betty Lee as she navigates the excitement and challenges of moving to a new town and starting high school, all while managing the responsibilities of being the eldest sibling in her family. Readers can expect themes of growth, friendship, and the transition from childhood to adolescence woven into the narrative. At the start of the story, we meet almost fourteen-year-old Betty as she prepares for the significant change of moving from her familiar hometown of Buxton to a new life in the city due to her father's business opportunity. Amidst the hustle and bustle of packing and goodbyes, Betty feels a mix of anxiety and excitement about her new adventure, including a daunting first day at a larger school filled with unfamiliar faces. The opening portion of the book introduces various family dynamics, establishes Betty's responsible nature, and hints at the challenges she will face adjusting to city life and high school social dynamics. (This is an automatically generated summary.)
Release date is 2010-12-08
Roger Frank and the Online Distributed Proofreading Team
Keywords: Schools -- Juvenile fiction; High school students -- Juvenile fiction; School sports -- Juvenile fiction; Students -- Juvenile fiction; Ninth grade (Education) -- Juvenile fiction